2019
DOI: 10.4187/respcare.07025
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Extubation Failure Related to Aspiration and/or Excessive Upper Airway Secretions

Abstract: and for the EVAKIN Study Group BACKGROUND: Extubation failure may have several causes, including swallowing dysfunction, aspiration, and excessive upper airway secretions. We hypothesized that a bedside global swallowing pattern assessment including 9 criteria (volume of pharyngeal secretions, 5 swallowing motor items, swallowing reflex, and 2 gag reflexes) performed prior to extubation could identify patients at risk of extubation failure. METHODS: In a multicenter prospective observational study, all consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
4
0
3
Order By: Relevance
“…Previous studies revealed that the prevalence of patients who failed in the process of ventilatory weaning, even after extensive evaluation of the extubation potential, varied between 5% and 30% (19,(21)(22)(23)(24)(25)(26) . It should be noted that these results reflect a different reality from the Brazilian one, since they are mostly data from international studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the prevalence of patients who failed in the process of ventilatory weaning, even after extensive evaluation of the extubation potential, varied between 5% and 30% (19,(21)(22)(23)(24)(25)(26) . It should be noted that these results reflect a different reality from the Brazilian one, since they are mostly data from international studies.…”
Section: Discussionmentioning
confidence: 99%
“…We also suggest performing a spontaneous breathing trial for better evaluation of extubation success. It is also important to test gag reflex and other airway protection reflexes before extubation, as there have been reports of re-intubation in patients with aspiration or excessive airway secretions, some of which require bronchoscopy ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, en la literatura se ha reportado la edad, la presencia de comorbilidades, el estado de conciencia, la falla cardiaca, el balance hídrico acumulado, el índice de oxigenación PaO2/FiO2, el puntaje APA-CHE II, los días en ventilación mecánica y la diuresis, entre otros, como factores de riesgo de destete ventilatorio fallido (16)(17)(18)(19).…”
Section: Discussionunclassified